Change of Muscle Activity as Well as Kinematic and Kinetic Parameters during Headers after Core Muscle Fatigue - Stephan Becker; Michael Fröhlich; Jens Kelm; Oliver Ludwig (MDPI AG, 2017)
In soccer, headers are a tactical measure and influenced by numerous factors. The goal of this study was to identify whether changes in kinematics and muscular activity, especially of the head-stabilizing muscles, occur during headers when the core musculature is fatigued. In two subgroups, muscular activity (12 amateur players, age 23.6 ± 4.2 years) and kinematics and dynamics (29 amateur players, age 23.7 ± 2.8 years) were examined during straight headers on a pendulum header. Data were collected before and after the core muscles were fatigued by an exercise program. Telemetric surface EMG, 3D acceleration sensor, force plate, and video recordings were used. Under fatigue, the activity of M. erector spinae and M. rectus abdominis was significantly reduced in the preparation phase of the header. The activity of M. sternocleidomastoideus was significantly increased during the jump phase, and the hip extension angle during maximum arched body tension was significantly reduced under fatigue. Jumping height, acceleration force impulse, and linear head acceleration were also significantly reduced. We conclude that fatigue of the core muscles affects the motion technique of the header and the activity of the muscle groups stabilizing the head. Therefore, the necessity of specific training in soccer should be emphasized from a medical-preventive point of view.